Structure and economic dimension of the book production process in Spain - Vázquez-Álvarez, Iñaki (Anuario ThinkEPI, 2022)
We carry out mesoeconomic and mesoanalytical analyses of the structure and economic dimension of the book production process in Spain. For this report, the following have been carried out: (1) 43 in-depth interviews with experts have been conducted; (2) the information provided by Panorámica de la edición española from 1996 to 2019 has been systematized; (3) financial information from 2,683 companies for the period 2019-2021 has been obtained through the Sistema de Análisis de Balances Ibéricos. The report contains: (1) an original and rigorous way of analyzing the book production process in Spain; (2) novel quantitative and qualitative information about publishing companies, as well as their suppliers of goods and services: editorial services, packagers, graphic arts divisions, the paper industry, and software providers; (3) relevant information about the context in which book production takes place in Spain and the national and international institutions involved.
Keywords: Book; Book industry; Publishing industry; Sectorial analysis; Mesoeconomics; Mesoanalysis; Spain